GIG WORKING DAN FWA TERHADAP JOB PERFORMANCE DIMEDIASI WORK ENVIROMENT DAN WLB - Rianty, Dewa Ayu Osa; Darma, Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025, 2025)
The high prevalence of gig workers in Indonesia and the preference for workplace flexibility among employees are significant concerns for companies, especially in human resource management. Therefore, this study focuses on job performance, hypothesized to be influenced by gig working and flexible working arrangements, mediated by work environment and work-life balance. The study population comprises all workers in Indonesia, with a sample of 120 respondents selected through purposive sampling. Data were analyzed using SEM-PLS methods. The findings indicate that both gig working and flexible working arrangements have a significant positive impact on employee performance in Indonesia. Gig working directly enhances performance, while flexible working arrangements influence performance through improved work environment and work-life balance. This suggests that the better the experience of gig working or perceived job flexibility among employees, the better their performance. This research can contribute to the improvement of job performance, emphasizing that employees are influenced by various factors in enhancing job performance. The findings of this study also provide practical contributions for companies regarding policies that need to be revised and established to improve job performance.